An audit of the nature and impact of clinical coding subjectivity variability and error in otolaryngology. (December 2013) - Nouraei, S.A.R.; Hudovsky, A.; Virk, J.S.; Chatrath, P.; Sandhu, G.S.
<x xml:space="preserve">Abstract</x> Objectives To audit the accuracy of clinical coding in otolaryngology, assess the effectiveness of previously implemented interventions, and determine ways in which it can be further improved. Design Prospective clinician–auditor multidisciplinary audit of clinical coding accuracy. Participants Elective and emergency ENT admissions and day‐case activity. Main outcome measures Concordance between initial coding and the clinician–auditor multi‐disciplinary teams (MDT) coding in respect of primary and secondary diagnoses and procedures, health resource groupings health resource groupings (HRGs) and tariffs. Results The audit of 3131 randomly selected otolaryngology patients between 2010 and 2012 resulted in 420 instances of change to the primary diagnosis (13%) and 417 changes to the primary procedure (13%). In 1420 cases (44%), there was at least one change to the initial coding and 514 (16%) health resource groupings changed. There was an income variance of £343, 169 or £109.46 per patient. The highest rates of health resource groupings change were observed in head and neck surgery and in particular skull‐based surgery, laryngology and within that tracheostomy, and emergency admissions, and specially, epistaxis management. A randomly selected sample of 235 patients from the audit were subjected to a second audit by a second clinician–auditor multi‐disciplinary team. There were 12 further health resource groupings changes (5%) and at least one further coding change occurred in 57 patients (24%). These changes were significantly lower than those observed in the pre‐audit sample, but were also significantly greater than zero. Asking surgeons to 'code in theatre' and applying these codes without further quality assurance to activity resulted in an health resource groupings error rate of 45%. The full audit sample was regrouped under health resource groupings 3.5 and was compared with a previous audit of 1250 patients performed between 2007 and 2008. This comparison showed a reduction in the baseline rate of health resource groupings change from 16% during the first audit cycle to 9% in the current audit cycle (P < 0.001). Conclusions Otolaryngology coding is complex and susceptible to subjectivity, variability and error. Coding variability can be improved, but not eliminated through regular education supported by an audit programme.